The effect of voluntourist motivation on satisfaction, continued volunteering, and intention to recommend volunteering in Indonesia - Nathania Silvana; Juliani Trisnawati (Faculty of Business and Economics, University of Surabaya, 2025)
Voluntourist motivation is an important factor that can influence satisfaction, continue volunteering, and intention to recommend in a non-profit organization in Indonesia. If the volunteer program does not meet expectations or fails to provide the experience expected by voluntourists, it will cause dissatisfaction. This study was conducted to determine the motivations of voluntourists in Indonesia and how they influence satisfaction, continue volunteering, and intention to recommend. This study is basic research with a quantitative approach. Respondent data was collected through Google Forms from a total of 220 people who had experience as volunteers in Indonesia. The data was then processed using the Partial Least Squares (PLS) approach using IBM SPSS 29 and SmartPLS 4 software. The results show that social (β = 0.160, p = 0.020), value (β = 0.280, p = 0.001), and environmental concern (β = 0.280, p = 0.004) are significant in relation to satisfaction, while career (β = 0.062, p = 0.384), enhancement (β = 0.043, p = 0.628), protective (β = 0.072, p = 0.394), and understanding (β = 0.035, p = 0.769) are not significant. Satisfaction is significant in relation to continuing volunteering (β = 0.707, p < 0.001) and intention to recommend (β = 0.696, p < 0.001).